EVALUATION OF POTENTIAL RISK POSED BY MEDICATIONS TO THE FETUS - S.A. Sher (Pediatričeskaâ Farmakologiâ, 2010)
The article focuses on the issue of evaluating potential risk posed by medications to the fetus during pregnancy. For this purpose various countries use classifications of medications broken down into risk categories during pregnancy. The most popular classification is US FDA classification, which identifies five categories of medications (А, В, С, D and Х) depending on the degree of their embryotoxic and teratogenic side effect, which enables physicians to make informed choices in selecting pharmacotherapy during the entire gestational period. The article discusses possible specific fetal and neonatal disorders when administering medications in categories X and D. Medications in category D may be prescribed to pregnant women only in extreme situations. Administering medications in category X is absolutely inadvisable before and during pregnancy. Further research in this area makes it possible to improve the classification of medications by degree of their embryotoxic and teratogenic risk and address the issue of selecting safe medications during pregnancy. Key words: medications, gestational period, embryo, fetus, embryotoxic and teratogenic action, fetal and neonatal disorders. (Pediatric Pharmacology. – 2010; 7(3):78-81)